Impact of Transformational Leadership Style of School Heads on Altruistic Citizenship Behaviour of Teachers: Evidence from Pakistani Secondary Schools - Muhammad Arif; Muhammad Arshad (JCTE, 2026)
Transformational leadership has been established as a key to organizational effectiveness improvement among school communities. Little has been researched about its direct impact on educators' altruistic citizenship behaviour, especially in countries such as Pakistan. It is a study about how high school heads' transformational leadership behaviour impacts teachers' altruistic citizenship behaviour in the southern districts of Khyber Pakhtunkhwa, Pakistan. Multi-staged stratified sampling method was applied to administer a quantitative survey. There were 30 school heads and 390 teachers who were participants from 40 secondary schools from four districts of the nation. Survey data collection employed the Multifactor Leadership Questionnaire (MLQ5X) and Organizational Citizenship Behaviour Scale (OCBS). Statistical procedures applied were descriptive statistics, analysis of variance (ANOVA), and regression analysis. It emerged that 55.8% of educators felt their heads to be displaying high degrees of transformational leadership. But 74.4% did not share the subsequent altruistic behaviour, and 25.6% remained neutral. Regression analysis indicated that transformational leadership had the most positive coefficient value (β = 0.616) to account for teachers’ altruistic behaviour, reflecting a considerable but complex relationship. The current study signals the possibility to promote transformational leadership to support teachers’ pro-social behaviour, but with problems related to implementation. Policymakers for education should strive to promote school heads’ skills to be transformational leaders to introduce positive organizational behaviour.